The Effect Of Different Kind of Packing Materials on The Carp (Leptobarbus hoevenii) Fish Atom Crackers Stored at Room Temperature for 30 Days - Akmin Sulaiman Harahap; N. Ira Sari; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was aimed to study the effect of different kind of packing materials on the quality of carp atom crackers stored at room temperature. The treatments in this research were different kind of packing materials which were polyprophylene, low density polyethylene and combination packing materials (HDPE and aluminium foil) and stored for H0 (0 day), H10 (10 days), H20 ( 20 days), H30( 30 days). The parameters used to analyze the quality of the fish atom crackers were organoleptic evaluation and chemis composition. The result showed that the carp fish atom cracker packed with combination packing materials (HDPE and aluminum foil) stored at room temperature for 30 days was the best treatment. It was showed by the highest organoleptic value and characterized with delicious and tasty (7,9), bright appearance (7,9), crispy and solid texture (7,6), aroma just like fish atom cracker (7,6). The carp atom crackers contained 3.14% moisture, 14.98% fat, and 5,11 mEq peroxide value.Keywords: Atom crackers, carp, packing materials, storage time